Effects of micro-alloying with lead for battery grid material. (15th November 2022) - Wall, Michael T.; Ren, Yang; Hesterberg, Travis; Ellis, Tim; Young, Marcus L.
Abstract: Pb-alloys are used as grid material for lead-acid batteries and have been implemented for years, and studying these Pb-alloys is critical to understanding the effects minor alloying additions on material characteristics. The current objective of this research is to evaluate the effects of minor alloying additions of Sb, As, Ca, Sn, Al, In, and Bi in Pb-alloy grid material during thermal cycling. In this study, Pb-grid material alloyed with a combination of elements mentioned above are examined using high-energy Synchrotron radiation X-ray diffraction measurements during in situ thermal cycling from RT to 75 °C to analyze grain inhibition and potential phase evolution. In addition, sulfation studies are performed in a solution of approximately 0.5 M H2 SO4 and the Pb-alloys are added to an electrochemical cell to undergo cyclic voltammetry. Results show In mitigates grain growth, and, during electrochemical testing, increases passivation of Pb-alloys. Bi causes increased grain growth during thermal cycling and promotes sulfate formation. Ca refines and stabilizes grains during thermal cycling and increases corrosion resistance during cyclic voltammetry testing. Sn and Al attribute to texturing in the material and increase corrosion rates. Highlights: In mitigates grain growth and increases passivation of Pb-alloys. Bi causes increased grain growth during thermal cycling and promotes sulfate formation. Ca refines and stabilizes grains and increases corrosion resistance. Sn and Al attribute to texturing in the material and increase corrosion rates.